Triptycene end-capped benzothienobenzothiophene and naphthothienobenzothiophene - Ueberricke, Lucas; Schwarz, Julia; Ghalami, Farhad; Matthiesen, Maik; Rominger, Frank; Elbert, Sven; Zaumseil, Jana; Elstner, Marcus; Mastalerz, Michael (Chemistry - a European journal, 2020)
Previously it was demonstrated that triptycene end-capping can be used as a crystal engineering strategy to direct the packing of quinoxalinophenanthrophenazines (QPPs) towards cofacially stacked π dimers with large molecular overlap resulting in high charge transfer integrals. Remarkably, this packing motif was formed under different crystallization conditions and with a variety of derivatives bearing additional functional groups or aromatic substituents. Benzothienobenzothiophene (BTBT) and its derivatives are known as some of the best performing compounds for organic field-effect transistors. Here, the triptycene end-capping concept is introduced to this class of compounds and polymorphic crystal structures are investigated to evaluate the potential of triptycene end-caps as synthons for crystal engineering.